2022
DOI: 10.3390/plants11091117
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure, Sources and Role of Bioactive Flavonoids in Cancer Prevention: A Review

Abstract: There has been a major shift in the collective mindset around the world in recent decades, both in terms of food and in terms of the treatment of chronic diseases. Increasing numbers of people are choosing to prevent rather than treat, which is why many consumers are choosing plant-based diets, mainly due to their bioactive compounds. A significant case of bioactive compound is flavonoids—a wide subclass of an even wider class of phytochemicals: polyphenols. Flavonoids are a broad topic of study for researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…A cohort study conducted by Wang et al reported that the amount of total polyphenols ranged from 8.88 to 47.44 mg/day in the lowest and highest quintile, respectively, among 38,408 middle-aged and old women [ 212 ]. Several studies have shown a correlation between polyphenols-rich diets and a reduced risk of cancer [ 213 , 214 ]. These polyphenols have similar properties in that they can act as antioxidants to scavenge ROS, which triggers pathways leading to cell cycle arrest, apoptosis induction, anti-inflammation, and anti-angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study conducted by Wang et al reported that the amount of total polyphenols ranged from 8.88 to 47.44 mg/day in the lowest and highest quintile, respectively, among 38,408 middle-aged and old women [ 212 ]. Several studies have shown a correlation between polyphenols-rich diets and a reduced risk of cancer [ 213 , 214 ]. These polyphenols have similar properties in that they can act as antioxidants to scavenge ROS, which triggers pathways leading to cell cycle arrest, apoptosis induction, anti-inflammation, and anti-angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The two aromatic rings A and B, which are joined by the C ring, which contains three carbon atoms, are consisting of fifteen carbon atoms (C6–C3–C6) in the fundamental chemical composition of flavonoids ( Fig. 4 ) [ 46 ]. Several investigations have revealed that flavonoids may defend against a variety of illnesses, including heart disease, cancer, neurological disease, as well as other age-related maladies.…”
Section: What Are Dietary Flavonoids?mentioning
confidence: 99%
“…), cereals (black rice, rye, black sorghum, purple barley, red sorghum, etc. ), chocolate, extra virgin olive oil, and beverages like green tea, black tea, red wine, and coffee [ 103 , 104 ].…”
Section: Human Intervention Studies Looking At the Effects Of Foods A...mentioning
confidence: 99%